Outcomes in relation to early parenteral nutrition use in preterm neonates born between 30 and 33 weeks' gestation: a propensity score matched observational study. Issue 2 (21st September 2021) - Webbe, James William Harrison; Longford, Nicholas; Battersby, Cheryl; Oughham, Kayleigh; Uthaya, Sabita N; Modi, Neena; Gale, Chris
Abstract : Objective: To evaluate whether in preterm neonates parenteral nutrition use in the first 7 postnatal days, compared with no parenteral nutrition use, is associated with differences in survival and other important morbidities. Randomised trials in critically ill older children show that harms, such as nosocomial infection, outweigh benefits of early parenteral nutrition administration; there is a paucity of similar data in neonates. Design: Retrospective cohort study using propensity matching including 35 maternal, infant and organisational factors to minimise bias and confounding. Setting: National, population-level clinical data obtained for all National Health Service neonatal units in England and Wales. Patients: Preterm neonates born between 30 +0 and 32 +6 weeks +days . Interventions: The exposure was parenteral nutrition administered in the first 7 days of postnatal life; the comparator was no parenteral nutrition. Main outcome measures: The primary outcome was survival to discharge from neonatal care. Secondary outcomes comprised the neonatal core outcome set. Results: 16 292 neonates were compared in propensity score matched analyses. Compared with matched neonates not given parenteral nutrition in the first postnatal week, neonates who received parenteral nutrition had higher survival at discharge (absolute rate increase 0.91%; 95% CI 0.53% to 1.30%), but higher rates of necrotising enterocolitis (absolute rate increase 4.6%), bronchopulmonary dysplasia (absolute rate increase 3.9%), late-onset sepsis (absolute rate increase 1.5%) and need for surgical procedures (absolute rate increase 0.92%). Conclusions: In neonates born between 30 +0 and 32 +6 weeks' gestation, those given parenteral nutrition in the first postnatal week had a higher rate of survival but higher rates of important neonatal morbidities. Clinician equipoise in this area should be resolved by prospective randomised trials. Trial registration number: NCT03767634 . Abstract : This is large study of over 16, 000 infants born between 30 and 32+6 weeks gestation. It compares those who received parenteral nutrition compared to those who did not and explores the risk and benefit of this intervention.